MULTI-FUNCTIONAL SOLAR-BASED GRAIN STORAGE DRYER: AN EQUIPMENT FOR EFFICIENT DRYING OF RICE GRAINS - Aquino, Adrian R.; Gapasangra, John Nazaren C.; Lawan, Khynne Mark Elmer B.; Solis Romnick B.; Talaman, Eduardo M. (Galaxy International Interdisciplinary Research Journal, 2023)
This study focused on determining the effectiveness of Multi-Functional Solar-Based Grain Storage Dryer in reducing and eliminating post-harvest risks that are present in sun drying. The researchers also aim to help the local farmers of Mauban, Quezon in increasing agricultural productivity through the use of modern technologies and renewable energy.